The Tone from Above: The Effect of Communicating a Supportive Regulatory Strategy on Reporting Quality - VAN DUIN, SANNE R.; DEKKER, HENRI C.; WIELHOUWER, JACCO L.; MENDOZA, JUAN P. (Journal of Accounting Research, 2018)
ABSTRACT In collaboration with the Authority for the Financial Markets in the Netherlands, we manipulate the content of official letters that instruct financial intermediaries to submit a mandatory self‐assessment. As part of the Registered Report Process, we submitted our hypotheses, experimental procedure, and planned statistical analyses before data collection. We predicted that a request indicating a supportive regulatory attitude has a positive effect on reporting quality on average. We also predicted this effect to be stronger for small firms and for firms with a long‐term orientation, and to become negative for firms with a short‐term orientation. Planned analyses show that a supportive letter reduced reporting quality unless firms had a long‐term orientation, supporting the moderating influence of time horizon, but providing no support for the expected average effect or for moderation by firm size.